Perilaku Coping Masyarakat Menghadapi Banjir - Khasan, Mohammad; Widjanarko, Mochamad (Jurnal Psikologi: PITUTUR, 2011)
Various  disasters  hit  Indonesia  causing death,  injury,  permanent  handicap, psychological trauma, and even harvest failure. Setrokalangan  Village  of  Kudus  Regency  is frequently flooded caused by the overflowing of Wulan River. The community is forced to have a coping  behaviour  in  dealing  with  the  flood  in order to survive.  The purpose of the research is to know the type and intensity of the coping behaviour of Setrokalangan community who are victims of flood.  Not all  individu  of  the  community  from Setrokalangan  Village  can  be  the  informant. Only those who have the specific identification which meets with research main problem can be  the  informants.  The identifications  are indigenous villagers of Setrokalangan Village, Kaliwungu  Sub-district,  Kudus  Regency  and victims of flood. Coping behaviour in the research refers to Lazarus & Folkman definition. Coping strategy is  divided  into  two,  problem  focused  coping (PFC)  and  emotional  focused  coping  (EFC), which  consist  of  8  forms  of coping  strategy. They are confrontation, social support, problem solving  plan,  self  control,  diversion,  positive value,  responsibility  to  be  taken,  running  or avoiding. Based on the coding of the interview and observation with three research informants, it can be concluded that the coping behaviour of the  community  of  Setrokalangan  Village  of Kudus  Regency  who  are  the  victims  of  flood tends to be confrontation, problem solving plan, self control, and running or avoiding.